Investigating the Factors Affecting Delays in Infrastructure Projects - Anurup Kakkar; Prakhar Duggal (International Journal of Engineering and Management Research, 2021)
Time and expense overruns are regular occurrences in the construction industry all around the world but these are a major concern in developing countries such as India, and their consequences can be extremely harmful when public infrastructure projects are concerned. In India as per the MoS & PI report, as of October 2019, there were 552 delayed construction projects, and the mean time overrun in these 552 delayed projects is29.07 months. Many studies in the literature review previously, have concentrated on a variety of infrastructure risk management issues but there have only been a few studies that have looked into the overall dynamics of infrastructure and how a project's timeline can be affected by changing risk interactions. This article aids in the investigation of the variables and causes of construction delays in infrastructure projects.